A Reclusive Foreign Body in the Airway: A Case Report and a Literature Review. (7th November 2013) - Philip, Ajay; Rajan Sundaresan, V.; George, Philip; Dash, Satyabrata; Thomas, Regi; Job, Anand; Anand, V. K.
Abstract : A foreign body in the larynx is an airway emergency that requires urgent evaluation and treatment. Irregular foreign bodies tend to orient in a sagittal plane and may produce only partial obstruction, allowing adequate air movement, hence making them undetectable for a long period of time. We report a case of a laryngotracheal foreign body that remained reclusive for 9 years.